2013
DOI: 10.1088/1751-8113/46/38/385202
|View full text |Cite
|
Sign up to set email alerts
|

‘Level grading’ a new graded algebra structure on differential polynomials: application to the classification of scalar evolution equations

Abstract: We define a new grading, that we call the "level grading", on the algebra of polynomials generated by the derivatives u k+i = ∂ k+i u/∂x k+i over the ring K (k) of C ∞ functions of u, u 1 , . . . , u k . This grading has the property that the total derivative and the integration by parts with respect to x are filtered algebra maps. In addition, if u satisfies an evolution equation u t = F [u] and F is a level homogeneous differential polynomial, then the total derivative with respect to t, D t , is also a filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Then, in [8] we showed that evolution equations with non-trivial ρ (i) , i = 1, 2, 3 are polynomial in u m−1 and u m−2 and possess a certain scaling property that we called "level grading" [9]. For m = 5, we have shown that there is a candidate for non-quasilinear integrable equation [1], we obtained canonical densities ρ (i) , i = 1, .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Then, in [8] we showed that evolution equations with non-trivial ρ (i) , i = 1, 2, 3 are polynomial in u m−1 and u m−2 and possess a certain scaling property that we called "level grading" [9]. For m = 5, we have shown that there is a candidate for non-quasilinear integrable equation [1], we obtained canonical densities ρ (i) , i = 1, .…”
Section: Introductionmentioning
confidence: 94%
“…The parts that has the highest level is called the "Top Level" part of P and the dependency of the coefficients of the top level on u b is called their "Top Dependency" [9].…”
Section: The "Level Grading"mentioning
confidence: 99%
See 1 more Smart Citation